Systematic Literature Review of Extensive Reading and Process-Oriented Reading Instruction (PORI) Strategy in EFL Contexts - Maulida, Ida; Boeriswati, Endry; Iskandar, Ifan (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Extensive Reading (ER) continues to be studied and improved not only for vocabulary acquisition comprehension, grammatical awareness but also in students’ motivation in EFL classroom learning. However, challenges arise due to the lack of structured reading guides. In this regard, the Process-Oriented Reading Instruction (PORI) strategy offers a step-by-step process that focuses on critical thinking and metacognitive reading strategies. This study aims to systematically examine the relationship between Extensive Reading (ER) and Process-Oriented Reading Instruction (PORI) strategies in teaching English as a Foreign Language (EFL) reading. The method used is the Systematic Literature Review (SLR) method guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review method. This study analyzes scientific publications sourced from Scopus, ERIC, and Google Scholar. This review is expected to contribute to the field of Language Education in the future by offering theoretical mapping and practical directions to develop a reading teaching model that is integrated with students' needs, especially to support curriculum innovation that is in education standards in Indonesia.